Original paperThe influence of undergone pecutaneous coronary interventions, and earlier hospitalizations with myocardial infarction on the level of knowledge and the effectiveness of health education in patients with acute myocardial infarction - Kubica, Aldona; Kochman, Wacław; Bogdan, Maria; Jurek, Aleksandra; Olejarczyk, Ewa; Magielski, Przemysław; Koziński, Marek; Grześk, Grzegorz; Wilczek, Rajmund; Sukiennik, Adam; Grześk, Elżbieta; Araszkiewicz, Aleksander (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2009)
Aim: To evaluate the influence of undergone pecutaneous coronary interventions and earlier hospitalizations with myocardial infarction on the level of knowledge about coronary artery disease and the effectiveness of health education. Methods: The study population consists of 146 consecutive patients with acute myocardial infarction treated with primary coronary intervention. The health education based on the specially prepared brochure was provided during hospitalization. The study population was divided into groups depend on undergone pecutaneous coronary interventions (PCI) (yes – n = 14, no – n = 132), and earlier hospitalizations with myocardial infarction (yes – n = 26, no – n = 120). Results: The increase of correct answers number after educational intervention was observed in patients non treated with PCI in the past (p = 0.005). The comparison of knowledge level in patients with and without history of PCI does not reveal any difference at the beginning and in the end of hospitalization. There was also no difference in the increase of correct answers number. The increase of correct answers number was significant (p = 0.01) in patients without myocardial infarction in the history. In the group of patients after myocardial infarction similar increase was observed, however it was not significant. In both groups the number of correct answers was similar in the first questionnaire, the same was observed in the second. Conclusions: Patients after PCI present higher level of knowledge at the beginning of hospitalization, however it does not increase during hospitalization in contrast to patients without PCI in the history, who revealed the significant knowledge improvement. Patients after myocardial infarction in the past do not differ in the level of knowledge in comparison to the others. They were not more prone to acquire important information for their health as well.